Parental Mental Health Association with Preschoolers' Social Skills in Urban Indonesia - Meriyandah, Hilda; Nurdiantami, Yuri; Shresta, Smarika; Li, Xiang; Zhu, Zhu; Shigeeda, Maiko; Anme, Tokie; Suryani, Rotua; Bunga, Dinda Nur Fajri Hidayati; Agustina, Lisna (Jurnal Parenting dan Anak, 2025)
Children's social development is an important aspect that influences their later life; hence it is important to optimize their development from an early age. This study investigates the correlation between development of social skills in preschool-aged children and parental mental health in Indonesia. Utilizing a cross-sectional observational methodology, data were gathered from 343 parents and teachers within nine private kindergartens located in SJ Ward, B City. The mental health of parents was examined with the Depression, Anxiety, and Stress Scale (DASS-21), whilst the social abilities of children were measured with the Social Skill Scale (SSS). Findings revealed a negative correlation between parental stress and anxiety with children's assertion, self-control, and cooperation. Nonetheless, depression did not exhibit significant correlations with social skills, which might be influenced by the study's cross-sectional design. The results underscore the necessity for early interventions aimed at alleviating parental stress and anxiety to enhance children's social skills. This research is the first application of the validated SSS for preschoolers in Indonesia, enhancing the comprehension of early childhood social development. Future investigations should examine long-term consequences via longitudinal studies. These findings offer significant insights for educators and mental health experts in formulating parenting support programs that promote healthy child development.